การสังเคราะห์โมโนกลีเซอไรด์ในเครื่องปฏิกรณ์ไมโครชนิดท่อคะพิลลารี - เมธี ศิริศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This work studied the hydrodynamic of immiscible liquid - liquid phase between glycerol and octanoic acid in capillary microreactor to find the optimum condition for monoglyceride synthesis. The percentage of selectivity of monoglyceride was also compared between capillary microreactor and a batch reactor. The hydrodynamic study provided the basic information such as flow regime, slug size and pressure drop which were related to input flow rate of glycerol and octanoic acid. The flow regime could be divided into 3 types including slug flow, drop flow and deformed flow. The slug flow showed a suitable pattern flow for monoglycerides synthesis because slug shape was stable and suitable for mass and heat transfers. The slug size was proportional to the input flow rate of glycerol and octanoic acid, while the pressure drop in capillary microtube was proportional to the slug flow velocity. Therefore, the optimum condition for synthesis monoglycerides in capillary microreactor was as follows: mole ration of glycerol to octanoic acid of 2 : 1 at 120 ℃ for min. Under this condition, the highest selectivity of monoglycerides (92.0%) was obtained Additionally, the selectivity of monoglycerides in microreactor was higher than in the batch Reactor due to better mass and heat trans transfers.